2006
DOI: 10.1248/bpb.29.1911
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Antioxidants from Sophora flavescens

Abstract: The objectives of this study were to investigate the radical-scavenging activity and protective potential of Sophora flavescens from oxidative damage by the radical generator 2,2-azobis(2-amidinopropane)dihydrochloride (AAPH) in renal epithelial LLC-PK 1 cells and to identify the active components using the bioassay-linked fractionation method. The MeOH extract and fractions of CH 2 Cl 2 , BuOH, and H 2 O from S. flavescens showed 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical-scavenging effects in a dose-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 25 publications
1
59
0
Order By: Relevance
“…12,20-24) Herein, we report some important physical data including 13 C-NMR spectroscopic data. 6 (q, C-9Љ), 111.6 (t, C-10Љ …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…12,20-24) Herein, we report some important physical data including 13 C-NMR spectroscopic data. 6 (q, C-9Љ), 111.6 (t, C-10Љ …”
Section: Resultsmentioning
confidence: 99%
“…1 H-and 13 C-NMR as well as 2D-NMR data were obtained on a Bruker AM 500 ( 1 H-NMR at 500 MHz, 13 C-NMR at 125 MHz) spectrometer (Bruker, Karlsruhe, Germany) in either CDCl 3 , acetone-d 6 …”
Section: ) Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, more than twenty alkaloids and fifty flavonoids have been isolated and identified (Miao & Zhang, 2001;Zhao & Sun, 2005). The dried roots of Sophora flavescens have various effects like anti-oxidant, anti-inflammation, anti-bacterial, apoptosis modulator properties and anti-tumor activities (Piao et al, 2006;Cheng, et al, 2006;Kuroyanagi et al, 1999;Ko et al, 2000;Zhang & Huang, 2004;Sun et al, 2007).…”
Section: Ethnopharmacological Usementioning
confidence: 99%
“…17) In addition, sophoraflavanone G and kurarinone exhibited protective effects against oxidative damage of the radical generator 2,2Ј-azobis-(2-amidinopropane)-dihydrochloride (AAPH) in renal epithelial LLC-PK(1) cells. 18) Moreover, in a previous study, we demonstrated the antioxidative properties of flavonoids from S. flavescens as 1,1Ј-diphenyl-2-picrylhydrazyl (DPPH) radical and ONOO Ϫ scavengers in vitro. 19) However, the cholesterol-lowering effects of S. flavescens in hyperlipidemic and hypercholesterolemic animal models have not been studied.…”
mentioning
confidence: 92%